2019
DOI: 10.3389/fcell.2019.00146
|View full text |Cite
|
Sign up to set email alerts
|

Models of Intracellular Transport: Pros and Cons

Abstract: Intracellular transport is one of the most confusing issues in the field of cell biology. Many different models and their combinations have been proposed to explain the experimental data on intracellular transport. Here, we analyse the data related to the mechanisms of endoplasmic reticulum-to-Golgi and intra-Golgi transport from the point of view of the main models of intracellular transport; namely: the vesicular model, the diffusion model, the compartment maturation–progression model, and the kiss-and-run m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 204 publications
(390 reference statements)
2
66
0
Order By: Relevance
“…Whereas studies in yeasts suggest the budding off of COPII-coated vesicles at the ERES as ERto-Golgi carriers (Dancourt and Barlowe, 2010;Kurokawa and Nakano, 2019;Lee et al, 2004), live imaging of mammalian cells has shown COPII coats stably associate with the ER (Mironov and Beznoussenko, 2019;Shomron et al, 2019;Stephens et al, 2000;Westrate et al, 2020). Our RUSH results are in line with the latter observations.…”
Section: Discussionsupporting
confidence: 88%
“…Whereas studies in yeasts suggest the budding off of COPII-coated vesicles at the ERES as ERto-Golgi carriers (Dancourt and Barlowe, 2010;Kurokawa and Nakano, 2019;Lee et al, 2004), live imaging of mammalian cells has shown COPII coats stably associate with the ER (Mironov and Beznoussenko, 2019;Shomron et al, 2019;Stephens et al, 2000;Westrate et al, 2020). Our RUSH results are in line with the latter observations.…”
Section: Discussionsupporting
confidence: 88%
“…Molecular mechanisms of anterograde cargo transport through the Golgi remain a major question in the field of membrane trafficking ( Malhotra et al, 1989 ; Glick and Malhotra, 1998 ; Glick and Luini, 2011 ; Beznoussenko et al, 2014 ; Mironov and Beznoussenko, 2019 ). In this context, there is still a big debate in the field about how anterograde cargo, such as MMPs that arrive in the cis-Golgi, are segregated from retrograde cargo trafficking to the ER ( Glick and Nakano, 2009 ; Mironov and Beznoussenko, 2019 ; Kurokawa et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, proteins may also affect the local membrane properties as external factors. Membrane-bound proteins such as coatomer (COP) I, COPII, dynamin, clathrin/AP1, clathrin/AP2, AP3, AP4 (reviewed in [ 26 , 33 , 34 , 35 ]), with asymmetric distribution of mass across the bilayer, influence membrane bending in a nonspecific manner due to molecular crowding [ 36 ]. Shallow hydrophobic insertions and strongly curved protein scaffolds appear to be effective generators of the membrane curvature of intracellular organelles [ 37 ].…”
Section: Factors Determining the Membrane Curvaturementioning
confidence: 99%